Life Support : Biocapital and the New History of Outsourced Labor - Vora, Kalindi, 1976- (Book collections on Project MUSE., 2015)
From call centers, overseas domestic labor, and customer care to human organ selling, gestational surrogacy, and knowledge work, such as software programming, life itself is channeled across the globe from one population to another. In Life Support, Kalindi Vora demonstrates how biological bodies have become a new kind of global biocapital. Vora examines how forms of labor serve to support life in the United States at the expense of the lives of people in India. She exposes the ways in which even seemingly inalienable aspects of human life such as care, love, and trust-as well as biological bodies and organs-are not only commodifiable entities but also components essential to contemporary capitalism. As with earlier modes of accumulation, this new global economy has come to rely on the reproduction of life for expansion. Human bodies and subjects are playing a role similar to that of land and natural resource dispossession in the period of capitalist growth during European territorial colonialism. Indeed, the rapid pace at which scientific knowledge of biology and genetics has accelerated has opened up the human body as an extended site for annexation, harvest, dispossession, and production.